Neonicotinoid trapping by the FA1 site of human serum albumin. Issue 4 (15th October 2019) - Leboffe, Loris; di Masi, Alessandra; Trezza, Viviana; Pasquadibisceglie, Andrea; Macari, Gabriele; Polticelli, Fabio; Ascenzi, Paolo
Abstract: Neonicotinoids are a widely used class of insecticides that target the acetylcholine recognition site of the nicotinic acetylcholine receptors in the central nervous system of insects. Although neonicotinoids display a high specificity for insects, their use has been recently debated since several studies led to the hypothesis that they may have adverse ecological effects and potential risks to mammals and even humans. Due to their hydrophobic nature, neonicotinoids need specific carriers to allow their distribution in body fluids. Human serum albumin (HSA), the most abundant plasma protein, is a key carrier of endogenous and exogenous compounds. The in silico docking and ligand binding properties of acetamiprid, clothianidin, dinotefuran, imidacloprid, nitenpyram, thiacloprid, and thiamethoxam to HSA are here reported. Neonicotinoids bind to multiple fatty acid (FA) binding sites, preferentially to the FA1 pocket, with high affinity. Values of the dissociation equilibrium constant for neonicotinoid binding FA1 of HSA (i.e., calc K n ) derived from in silico docking simulations (ranging between 3.9 × 10 −5 and 6.3 × 10 −4 M) agree with those determined experimentally from competitive inhibition of heme‐Fe(III) binding (i.e., exp K n ; ranging between 2.1 × 10 −5 and 6.9 × 10 −5 M). Accounting for the HSA concentration in vivo (~7.5 10 −4 M), values of K n here determined suggest that the formation of the HSA:neonicotinoid complexes may occur in vivo. Therefore, HSA appears to be an important determinant for neonicotinoid transport and distribution to tissues and organs, particularly to the liver where they are metabolized.